1991
DOI: 10.1177/000992289103000101
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Parents' Concerns About Their Child's Behavior

Abstract: Parents often complain about children's behavior. Pediatricians may be unsure whether to ignore these complaints, counsel parents in-office or refer them to mental health services. This study shows a close relationship between parents' concerns and measurably significant behavior problems. Methods are provided for responding to parents' concerns. These should be useful to pediatricians who are often criticized for failing to detect and refer children with mental health problems including behavior disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
7

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 13 publications
5
81
0
7
Order By: Relevance
“…. "y"en: Djfficult 75 (57) 50 (38) 6 (5) 1 (1) o (48) 49 (44) 8 (7) 1 (1) o Completion rate and the parental ranking of the ASQ and the CD!. To collect data on the parent' s opinion of the questionnaire, the qqestion-" Did you find this questionnaire easy to complete?…”
Section: Communicationmentioning
confidence: 99%
“…. "y"en: Djfficult 75 (57) 50 (38) 6 (5) 1 (1) o (48) 49 (44) 8 (7) 1 (1) o Completion rate and the parental ranking of the ASQ and the CD!. To collect data on the parent' s opinion of the questionnaire, the qqestion-" Did you find this questionnaire easy to complete?…”
Section: Communicationmentioning
confidence: 99%
“…[71][72][73][74] Early diagnosis of ASD is dependent on listening to the parents' concerns about their child's development. Two studies from the United Kingdom have demonstrated that most parents of children later diagnosed with ASD first became concerned about their child's development around 18 months old.…”
Section: Screening and Surveillancementioning
confidence: 99%
“…Crianças com este tipo de alteração apresentam maior risco de evoluírem com dificuldades de aprendizagem, idiossincrasias comportamentais, tendência ao isolamento social, baixa performance em atividades físicas ou motoras e sofrimento psíquico (Glascoe, 2000;Hamilton 2006;Mallhi & Singhi, 1999;Glascoe, 1991, Bayoglu et al, 2007.…”
Section: A Magnitude Do Problemaunclassified
“…Quanto mais precoce esta intervenção (abaixo dos dois anos), melhores os resultados (First & Palfrey, 1994;Tough et al, 2006;Miranda et al, 2003;Majnemer, 1998;Reynolds et al, 2007;OMS, 2001;OPAS, 2005;Glascoe, 1991;Glascoe, 2000;Schneider & Ramires, 2007;NHMRC, 2002;USPSTF, 2006;AAP, 2001;AAP, 2006;Engle et al, 2007;Hertzman & Wiens, 1996).…”
Section: A Magnitude Do Problemaunclassified
See 1 more Smart Citation